from the sum of 2x²+3xy-x²-xy-y² &xy+2y² subtract the sum of 3x²-y² &-x²+ xy+y²
Answers
Answered by
5
Answer:
7x² - 6y²+ 6xy
Step-by-step explanation:
Subtract the sum of x²–5xy+2y² and y²–2xy–3x² from the sum of 6x²–8xy–y² and 2xy–2y²–x²
A = sum of x²–5xy+2y² and y²–2xy–3x²
B = sum of 6x²–8xy–y² and 2xy–2y²–x²
we need to find
S = B - A
B = 6x²–8xy–y² + 2xy–2y²–x²
=> B = 5x² - 3y²- 6xy
A = x²–5xy+2y² + y²–2xy–3x²
=> A = -2x²–7xy+3y²
S = B - A
=> S = 5x² - 3y²- 6xy - (-2x²–7xy+3y²)
=> S = 5x² - 3y²- 6xy + 2x²+7xy-3y²
=> S = 7x² - 6y²+ 6xy
Similar questions